Transformacja handlu detalicznego Fast Moving Consumer Goods (FMCG) w Polsce po 1989 roku - Kondej, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of the article is to present and analyze the deep transformations that have occurred in the retail trade of the FMCG in Poland after 1989. It presents the phase nature of the transformations of this market, which led to its current diversified structure. Both the development of domestic trade and the expansion of foreign trade corporations were taken into account. The content includes issues such as market diversification and concentration, development within particular formats and the phenomenon of convergence. The paper takes advantage of ongoing qualitative and quantitative research (since 2012) of the FMCG retail market in Poland by Kondej Marketing. The survey is based on aggregation and analysis of available secondary data, market observations and primary direct interviews. Particular emphasis is placed on the impact of the demand factor on the development and shaping of the structure of this market. The influence of disposable income on the situation within the retail market of the FMCG industry was comprehensively presented. The preferences and purchasing behavior of Polish consumers, which are unique on a European scale, were also taken into account. This applies, in particular, to the attitude of smart shopping and the tendency to buy in stores located near buyers’ place of residence. The article presents the thesis that the purchasing preferences of Polish consumers have a significant impact on the development of the sector and its structure.